Green approach for selective Cu(II) recovery from aqueous solutions: Efficient separation from Ni(II) and Co(II) with organic phase regeneration - Chang, Siu Hua; Abdul Halim, Siti Fatimah; Abdul Halim, Muhammad Ikram; Morad, Norhashimah (Asia-Pacific Journal of Science and Technology, 2025)
The objective of this study was to achieve the selective recovery of Cu(II) from aqueous solutions in the presence of Ni(II) and Co(II) by utilising a green approach, palm kernel fatty acid distillate (PKFAD) as the organic phase. PKFAD was employed without the use of diluent, extractant, or modifier typically required in conventional solvent extraction processes. In the first stage of the procedure, Cu(II) was selectively extracted and stripped from the multi-element solution. In the second stage, Ni(II) and Co(II) were subsequently recovered. The selectivity of the extraction process was driven by the difference in pH-dependence equilibrium (pHeq) for each metal ion. A high Cu(II) efficiency of 97% was achieved in the first stage at pHeq of 4.8, while Ni(II) and Co(II) extraction efficiencies of 88% and 85%, respectively, were obtained in the subsequent extraction stage at a pHeq of 5.9. Separation factor for Cu(II) over Ni(II) and Co(II) were ≥ 180, indicating effective selective separation. Additionally, the PKFAD was successfully regenerated, with the stripping process achieved 98% of Cu(II), 85% of Ni(II) and 72% of Co(II) recovery. These results highlight the efficacy of PKFAD as a sustainable, regenerable organic phase with high potential for selective metal ion recovery.